Theoretical aspects of project management of university staff and climate in the team - D. Y. Polenov; G. K. Mukhanova; S. A. Sataev (Экономика: стратегия и практика, 2020)
Currently, the Republic of Kazakhstan is increasing interest in project management and the project approach to the management of educational institutions. However, due to the novelty of this approach, not everyone is familiar with its basic theoretical and practical approaches, including management with employees of educational institutions. Today, the problem of inconsistent approaches to managing educational institutions with the realities that society expects from schools, colleges, and universities has become very obvious and understandable.The purpose of the study conducted in this article is to consider the theoretical and practical aspects of the application of project management approaches to the personnel management of educational institutions and determine the level of awareness of the project approach.As a research method to achieve the goals in this article, a round-robin analysis method with the collection of quantitative data was chosen. The results of a quantitative study of employees of educational institutions allow us to conclude that not all educational workers are aware of the benefits of a project-based approach to university personnel management, which is likely to affect the effectiveness of educational organizations themselves, as well as to conclude that that the principle of a collective project approach to personnel management can serve as a driver for raising the level of quality of educational services provided means of greater involvement of university employees.